The Alkamide trans-Pellitorine Targets PPARγ via TRPV1 and TRPA1 to Reduce Lipid Accumulation in Developing 3T3-L1 Adipocytes - Lieder, Barbara; Zaunschirm, Mathias; Holik, Ann-Katrin; Ley, Jakob P.; Hans, Joachim; Krammer, Gerhard E.; Somoza, Veronika (Frontiers in Pharmacology, 2017)
Adipose tissue is an important endocrine organ in the human body. However, pathological overgrowth is associated with chronic illness. Regulation of adipogenesis and maturation of adipocytes via bioactive compounds in our daily diet has been in focus of research in the past years and showed promising results for agonists of the ion channels transient receptor potential channel (TRP) V1 and A1. Here, we investigated the anti-adipogenic potential and underlying mechanisms of the alkamide trans-pellitorine present in Piper nigrum via TRPV1 and TRPA1 in 3T3-L1 cells. trans-Pellitorine was found to suppress mean lipid accumulation, when applied during differentiation and maturation, but also during maturation phase solely of 3T3-L1 cells in a concentration range between 1 nM and 1 µM by up to 8.84±4.97% or 7.49±5.08%, respectively. Blockage of TRPV1 using the specific inhibitor trans-tert-butyl-cyclohexanol demonstrated that the anti-adipogenic activity of trans-pellitorine depends on TRPV1. In addition, blockage of the TRPA1 channel using the antagonist AP-18 showed a TRPA1-dependent signaling in the early to intermediated stages of adipogenesis. On a mechanistic level, treatment with trans-pellitorine during adipogenesis led to reduced PPARgamma expression on gene and protein level via activation of TRPV1 and TRPA1, and increased expression of the micro-RNA mmu-let7b, which has been associated with reduced PPARgamma levels. In addition, cells treated with trans-pellitorine showed decreased expression of the gene encoding for fatty acid synthase, increased expression of micro-RNA-103 and a decreased short-term fatty acid uptake on the functional level. In summary, these data point to an involvement of the TRPV1 and TRPA1 cation channels in the anti-adipogenic activity of trans-pellitorine via micro-RNA-let7b and PPARgamma. Since trans-pellitorine does not directly activate TRPV1 or TRPA1, an indirect modulation of the channel activity is assumed and warrants further investigation.